A review of studies on mass-movements on the Moon - Li, Kaixuan; Wang, Jiao; Shi, Yijian (Frontiers in Astronomy and Space Sciences, 2023)
The study of the lunar surface is a significant field in exploring the Moon. As a non-negligible geological process shaping the lunar surface, however, the mass movements on the Moon haven't been deeply studied regarding all available datasets. In this paper, we report the results of the literature review and quantitative analysis of 965 articles retrieved from the Scopus, WoS, and ADS databases using keyword search terms between the years 1872 and 2022. The main findings show that the lunar mass movements are a lasting but recent prosperous research topic (since 2009). The top three influential journals in this area are Icarus, JGR, and P&SS. Robinson, Lucchitta, and Carr are the most three productive authors. California Institute of Technology, Arizona State University, and Johns Hopkins University are active institutions leading the lunar mass movements research, and the related institutions are mainly located in the USA, Russia, and China. Articles are primarily published in journals specializing in the fields of astronomy and physics. The index analysis of citation indicates the growth of the academic impact of articles about the lunar mass movements. This article summarizes the datasets, methods, and relevant parameters of lunar mass movements to facilitate future research, as well as discussing the limitations and trends in the field. In addition, four unsolved issues are proposed, including: 1) the lack of a comprehensive global database that records all types of landslides incidents; 2) the need for definite classification indicators to quantify the classification criteria for lunar mass movements; 3) the absence of a mathematical model to explain the triggering mechanism of mass movements on the Moon; and 4) the lack of quantitative indexes to evaluate the modification effect of mass movements on the lunar surface morphology. With the support of big data, the combination of artificial intelligence and traditional GIS methods is expected to become the main approach for addressing these issues Such a bibliometric analysis can inspire future researchers by exploring the overall characteristics of the published literature on lunar mass movements.